Impacts of pollution discharges from Dinh Vu industrial zone on water quality in the Hai Phong coastal area - Vinh, Vu Duy; Hai, Nguyen Minh; Khanh, Do Gia (Vietnam Journal of Marine Science and Technology, 2020)
The hydrodynamic and water quality models (the Delft3D model) were established based on the measured data and the estimated pollution discharges from Dinh Vu industrial zones to Nam Trieu estuary. With seven separate simulation scenarios, the results show that in case of increased wastewater with the control of pollution discharge (water and concentration), the impact of pollution is only limited to a small area around the discharge point. Their influences on water quality in other areas in Nam Trieu estuary are quite small. Meanwhile, in case of environmental risk, a strongly increasing pollution load would cause the significantly increasing pollutant concentration in this area, they have almost exceeded the value in the National Technical Regulation on surface water quality (QCVN 10-MT:2015/BTNMT), such as NH4, COD, and BOD. Dissolved oxygen in the water would also decrease significantly. The spatial influence extends from the discharge point to Nam Trieu estuary, inside Cam, Bach Dang rivers, and Cat Hai coastal area.